2013
DOI: 10.1021/jf4031585
|View full text |Cite
|
Sign up to set email alerts
|

Olive (Olea europaea L.) Tree Nitrogen Status Is a Key Factor for Olive Oil Quality

Abstract: The influence of macronutrient status on olive oil properties was studied for three years. Data were analyzed by a multivariate model considering N, P, K, and fruiting year as explanatory factors. Oil quality parameters were primarily associated with N concentration in leaves and fruits which increased with N in irrigation solution. The effect of P on oil quality was mainly indirect since increased P availability increased N accumulation. The potassium level had negligible effects. The oil phenolic content dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 42 publications
9
59
0
2
Order By: Relevance
“…Our results indicate that olive nutritional status and harvest parameters are important for oil quality in agreement with Erel et al. (). Olive trees with heavy loads slow down the ripening process ( Trentacoste et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that olive nutritional status and harvest parameters are important for oil quality in agreement with Erel et al. (). Olive trees with heavy loads slow down the ripening process ( Trentacoste et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile in other experiments, a reduction in linoleic acid coincided with N-application, and, consequently, a decrease in the relation between UNFA and SAFA was observed (Toplu et al, 2009). Erel et al (2013) reported that the level of desaturation for the three major C18 fatty acids (oleic, linoleic and linolenic acids) increased with fruit N-content. However, these authors pointed out that no solid linkage between N and oleatedesaturase could be found in the literature and the N-level may indirectly affect desaturation via assimilate availability.…”
Section: Discussionmentioning
confidence: 99%
“…Under high N conditions, the synthesis of proteins demands a high amount of the precursor, reducing the synthesis of phenols and hence polyphenols. In olives it has been observed by Erel et al (2013) that fruit phenol content is inversely related with N in leaf, and they suggested that either phenol precursors or polyphenols themselves could be produced in leaves and translocated to the fruit, and it is on the leaves where the competition between both pathways occurred. These authors obtained a negative relationship between high nutritional N-doses and oil quality in olive trees, and observed that when N content in leaves increased, oleic acid and polyphenol content were reduced, negatively affecting oil quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation with RWW, while using routine fertilization regimes not considering nutrients delivered with the water, might expose plants to excess levels of the macronutrients N, P and K . Previous works showed that olive oil composition and quality are remarkably affected by the amounts of N and P, while K has a minor effect . Total phenolics content (TPC) decreased in response to fertilization with high levels of N .…”
Section: Introductionmentioning
confidence: 99%